2018
DOI: 10.1515/hsz-2018-0235
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric plasma is a viable solution for treating orthopedic infection: a review

Abstract: Bacterial infection and antibiotic resistance are major threats to human health and very few solutions are available to combat this eventuality. A growing number of studies indicate that cold (non-thermal) plasma treatment can be used to prevent or eliminate infection from bacteria, bacterial biofilms, fungi and viruses. Mechanistically, a cold plasma discharge is composed of high-energy electrons that generate short-lived reactive oxygen and nitrogen species which further react to form more stable compounds (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 90 publications
0
18
0
Order By: Relevance
“…It can be achieved by energizing gases like inert gases such as argon or by ionising the ambient air to create reactive components with multiple effects. Many authors have described the positive effect of CAP in accelerating wound healing, erasing bacteria or reducing candida [31][32][33][34][35]. Incidentally, the effect of CAP on critical cell functions is linked with active plasma components [36].…”
Section: Introductionmentioning
confidence: 99%
“…It can be achieved by energizing gases like inert gases such as argon or by ionising the ambient air to create reactive components with multiple effects. Many authors have described the positive effect of CAP in accelerating wound healing, erasing bacteria or reducing candida [31][32][33][34][35]. Incidentally, the effect of CAP on critical cell functions is linked with active plasma components [36].…”
Section: Introductionmentioning
confidence: 99%
“…CAP is a low-temperature ionized or partially ionized gas (approximately 20-40 ℃) that makes it suitable for use in living cells and tissues (68,69). Recent studies have shown that CAP's antibacterial action is mainly the production of long-and short-lived active substances (ROS and reactive nitrogen species) (70)(71)(72)(73)(74). CAP treatment can be divided into direct treatment and activated-liquid treatment (71).…”
Section: Cold Atmospheric Plasma (Cap)mentioning
confidence: 99%
“…Direct therapy is done using devices that directly touch cells or the body. CAP device-activated fluids, or cap-activated fluids, have strong therapeutic potential similar to the effects of direct CAP therapy (73). Studies found that CAP treatment increased intracellular ROS levels, which was even greater during direct treatment.…”
Section: Cold Atmospheric Plasma (Cap)mentioning
confidence: 99%
“…CAP operates at body temperature, making it feasible for a variety of medical applications, such as chronic wound treatment; skin disinfection [16][17][18]; tissue regeneration in chronic leg ulcers [19]; dentistry [20]; in dermatology for the treatment of tumours, actinic keratosis, scars, ichthyosis, psoriasis, atopic eczema, as well as for alleviation of pain and itch [21][22][23]; and in haematology for blood coagulation [24,25]; in ophthalmology (human corneas) [26]. Recently there has been increased interest in clinical applications in anticancer therapy as a novel promising treatment [27], leading to a new field of medicine called "plasma oncology or plasma medicine" [8,28,29].…”
Section: Introductionmentioning
confidence: 99%